A modified zinc alloy with a zinc phosphate film on the surface, and its preparation method and application

The zinc phosphate film was prepared by chemical conversion method using phosphoric acid and nitric acid solutions on the surface of zinc alloy, which solved the problem of excessive release of zinc ions on the surface of zinc alloy, improved its biocompatibility and antibacterial properties, and achieved better clinical application effects .

CN115838925BInactive Publication Date: 2025-01-14SHANDONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211594823.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-13
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the zinc phosphate chemical conversion membrane has not been effectively prepared on the surface of zinc alloy, resulting in excessive release of zinc ions affecting the cytocompatibility and antibacterial properties of zinc alloys.

Method used

By adding phosphoric acid solution and nitric acid solution to the chemical solution, a zinc phosphate chemical conversion film is prepared on the surface of the zinc alloy by chemical conversion method, and zinc ions in the zinc alloy matrix participate in the reaction to form a dense and uniform zinc phosphate film layer to inhibit the zinc ions. Excessive release.

Benefits of technology

It improves the biocompatibility and antibacterial properties of zinc alloys, improves its clinical application effect, and realizes low-cost film preparation through a simple room temperature process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115838925B_ABST
    Figure CN115838925B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of surface modification of biomedical metal materials, and specifically relates to a modified zinc alloy coated with a zinc phosphate film layer on the surface, and a preparation method and application thereof. The present invention provides a modified zinc alloy coated with a zinc phosphate film layer on the surface, comprising a zinc alloy as a substrate and a zinc phosphate chemical conversion film attached to the surface of the zinc alloy substrate; the main phase composition of the zinc phosphate chemical conversion film is zinc phosphate. The zinc phosphate chemical conversion film of the present invention can inhibit the excessive release of zinc ions during the degradation of the zinc alloy, achieve effective protection of the zinc alloy substrate, improve the biocompatibility and antibacterial properties of the zinc alloy, and has potential significance for further improving the clinical application effect of zinc alloy substrate implants.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with an application date of July 13, 2021, application number 202110789515.4, and invention name "A zinc phosphate chemical conversion film on the surface of zinc alloy, its preparation method and application". Technical Field

[0002] The invention relates to the field of surface modification of biomedical metal materials, and in particular to a zinc phosphate chemical conversion film on the surface of a degradable zinc alloy and a preparation method thereof. Background Art

[0003] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0004] Zinc and zinc alloys have become a promising biodegradable metal due to their important physiological effects and good degradation properties. The strength and plasticity of zinc alloys have been significantly improved, making up for the shortcomings of pure zinc in mechanical properties. However, during the degradation process, the excessive release of zinc ions affects the cell compatibility and antibacterial properties of zinc alloys. Therefore, surface modification of zinc alloys to give them biofunctionalized surfaces is an effective means to further improve their cell compatibility and antibacterial properties. The phosphate chemical conversion method can generate an insoluble film layer on the metal surface through chemical and electrochemical reactions at the interface between the base metal and the solution. The film layer prepared by this method is mainly composed of phosphate phase. By designing the conversion process parameters, a film system with different phases, components and structures can be obtained.

[0005] Zinc is an essential element for the human body and can participate in many important physiological functions. Zinc ions can promote the differentiation of osteoblasts and inhibit the differentiation of osteoclasts, and play an important role in stimulating bone growth and mineralization. In addition, zinc can inhibit bacterial infection and maintain cardiac function through redox signaling pathways. Therefore, the preparation of zinc-containing phosphate conversion film on the surface of degradable zinc alloy can give the zinc alloy a biofunctionalized surface and improve its biocompatibility and antibacterial properties. The surface morphology and structure of the material can significantly affect the blood compatibility, cell compatibility and antibacterial properties. At present, it has been reported that the micro / nanoscale coating structure can significantly improve the viability, adhesion and differentiation of preosteoblasts and vascular endothelial cells, and significantly reduce the adhesion of platelets and Escherichia coli. The biofunctionalized film layer can improve the biocompatibility and antibacterial properties of the material and control the degradation rate.

[0006] In the prior art, there are many methods for preparing chemical conversion films on the surface of titanium and titanium alloys. For example, a titanium substrate is pretreated with a strong alkaline solution and then chemically converted, and finally a titanium zinc phosphate chemical conversion film is obtained by heat treatment; a zinc phosphate conversion is completed by applying a current field to obtain a zinc phosphate conversion film on the titanium surface; a pretreated substrate titanium or titanium alloy is coupled with a metal with a relatively low corrosion potential, and a chemical conversion film on the surface of titanium and titanium alloy is obtained by chemical conversion after coupling.

[0007] At present, the method of preparing chemical conversion film on the surface of titanium and titanium alloys is relatively mature, but how to prepare zinc phosphate chemical conversion film on the surface of zinc alloy has not been reported. Summary of the invention

[0008] In order to solve the problems in the prior art, the present invention proposes a zinc phosphate chemical conversion film on the surface of a zinc alloy and a preparation method and application thereof, and realizes the preparation of a zinc phosphate chemical conversion film on the surface of a degradable zinc alloy by adding a film-forming substance to a chemical liquid. By coating with a zinc phosphate film layer, the biocompatibility and antibacterial properties of the zinc alloy substrate are further improved, thereby improving its clinical application effect.

[0009] In order to solve the above technical problems, the technical solution of the present invention is:

[0010] A first aspect of the present invention provides a chemical conversion solution for forming a zinc phosphate chemical conversion film on a zinc alloy. The chemical conversion solution includes a phosphoric acid solution and a nitric acid solution.

[0011] The second aspect of the present invention provides a method for preparing a zinc phosphate conversion film on the surface of a zinc alloy, using the above-mentioned chemical conversion solution to prepare a zinc phosphate conversion film on the surface of the zinc alloy by a chemical conversion method;

[0012] The third aspect of the present invention provides a zinc phosphate chemical conversion film on the surface of a zinc alloy, which is prepared by the above method.

[0013] A fourth aspect of the present invention provides a surface-modified zinc alloy, comprising a zinc alloy substrate and a zinc phosphate chemical conversion film attached to the surface of the zinc alloy substrate.

[0014] The fifth aspect of the present invention provides the use of the surface modified zinc alloy as an implant material.

[0015] One or more embodiments of the present invention have the following beneficial effects:

[0016] (1) Based on the unique biological function of zinc, the present invention prepares a biofunctional film layer composed of zinc phosphate crystal phase on the surface of zinc alloy by phosphate chemical conversion method. The chemical conversion film gives the zinc alloy a biofunctional surface, improving its biocompatibility and antibacterial properties.

[0017] (2) The present invention endows the zinc alloy substrate with a biofunctional surface. The prepared zinc phosphate coating is not only dense and uniform, but also has fine zinc phosphate crystal particles, which can effectively protect the zinc alloy substrate and inhibit the excessive release of zinc ions, thereby improving the biocompatibility and antibacterial properties of the zinc alloy, and has potential significance for further improving the clinical application effect of zinc alloy substrate implants.

[0018] (3) The preparation method of the present invention can be completed at room temperature, has a simple process and low cost, and the obtained film layer is uniform and complete, with fine and dense grains.

[0019] (4) In the present invention, the zinc ions are provided by the zinc alloy matrix, and no external zinc source is required. By adjusting the conversion time, the preparation of a continuous zinc phosphate film can be achieved without changing the film layer elements and phase composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 This is an X-ray diffraction diagram of the zinc phosphate chemical conversion film on the surface of the zinc alloy prepared in Examples 1-4 of the present invention.

[0022] Figure 2 Field emission scanning electron microscope images of zinc phosphate chemical conversion films on the surfaces of zinc alloys prepared in Examples 1-4 of the present invention;

[0023] Figure 2 A is a field emission scanning electron microscope image of the zinc phosphate chemical conversion film on the zinc alloy surface prepared in Example 1.

[0024] Figure 2 B is a field emission scanning electron microscope image of the zinc phosphate chemical conversion film on the zinc alloy surface prepared in Example 2.

[0025] Figure 2 Figure C is a field emission scanning electron microscope image of the zinc phosphate chemical conversion film on the zinc alloy surface prepared in Example 3.

[0026] Figure 2 D in the figure is a field emission scanning electron microscope image of the zinc phosphate chemical conversion film on the zinc alloy surface prepared in Example 4. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0029] In order to solve the problem that the cell compatibility and antibacterial properties of zinc alloy are affected due to excessive release of zinc ions during the degradation process of zinc alloy.

[0030] The first aspect of the present invention provides a chemical conversion solution for forming a zinc phosphate chemical conversion film on a zinc alloy, the chemical conversion solution comprising a phosphoric acid solution and a nitric acid solution. In the process of preparing the conversion film on the surface of a titanium and titanium alloy substrate, a dense oxide film is easily formed on the substrate surface. Due to the protective effect of the dense oxide film, the titanium and titanium alloy substrates only provide a potential difference during electrical coupling, but do not participate in the conversion reaction. The inventors have found that the degradable zinc alloy can provide a certain amount of zinc ions by degradation during the conversion process, and this part of the zinc ions can directly participate in the chemical reaction to form a chemical conversion film. The chemical conversion solution of the present application does not provide zinc ions. The zinc phosphate chemical conversion film of the present application, the substance that provides zinc ions is the zinc alloy substrate, and no external zinc source is required. The chemical conversion solution of the present application is simple in composition, which can prevent the introduction of other cations to participate in the formation of the film layer, thereby interfering with the formation of the zinc phosphate crystal phase. The nitric acid solution not only participates in the film formation, but also can act as a promoter when introduced, and will not affect the phase composition of the film layer.

[0031] In some embodiments, the chemical conversion solution further comprises a promoter, preferably, the promoter is Ca(NO 3 ) 2 ·4H 2 O、NaClO 3 、NaNO 3 , C 6 H 8 O 7 ·H 2 O; preferably, the concentration of each substance in the chemical conversion solution is: phosphoric acid 0.1-0.3 mol / L, nitric acid 0.3-0.6 mol / L, and promoter 0.01-0.1 mol / L. Adding promoter can accelerate the reaction process, shorten the reaction time, and improve the density and uniformity of the film layer while promoting film formation, thereby optimizing the microstructure of the film layer. The substance involved in film formation is H 3 PO 4 and HNO 3 While providing phosphate, it is necessary to avoid introducing other cations to participate in the film formation and thus interfere with the formation of zinc phosphate crystal phase. Zn ions can participate in the film formation, while Na ions do not participate in the film formation and thus do not interfere with the reaction process.

[0032] The second aspect of the present invention provides a method for preparing a zinc phosphate conversion film on the surface of a zinc alloy, using the above-mentioned chemical conversion solution to prepare a zinc phosphate conversion film on the surface of the zinc alloy by a chemical conversion method;

[0033] Preferably, the substance providing phosphate ions is H 3 PO 4 ; The substance that provides zinc ions is a zinc alloy matrix.

[0034] In some embodiments, the chemical conversion liquid is treated with iron powder reduction to obtain a aging liquid, and the zinc alloy substrate is coupled with the iron clamp and then immersed in the aging liquid for chemical conversion treatment to obtain a chemical conversion film;

[0035] Preferably, the method for aging the chemical conversion liquid with reduced iron powder is: adding 1-5 g of reduced iron powder to the chemical conversion liquid, and aging at 20-35° C. for 12-24 hours to obtain an aging liquid;

[0036] Preferably, the temperature of the chemical conversion treatment is 20-35°C, and the conversion time is 30s-60min. Further preferably, the conversion time is 30s-15min. After the chemical conversion liquid is aged by reduced iron powder, the resulting aged liquid contains a certain amount of ferrous ions. Ferrous ions can play a specific catalytic role, accelerate the chemical conversion process, and further promote the formation of phosphate crystal phase on the surface of the zinc alloy matrix.

[0037] In some embodiments, a degradable zinc phosphate chemical conversion film on the surface of zinc alloy and a preparation method thereof include the following steps:

[0038] preparing a chemical conversion liquid, mixing the phosphorus-containing compound and the accelerator, etc. to obtain the chemical conversion liquid;

[0039] The chemical conversion liquid is subjected to a reduction iron powder aging treatment to obtain an aging liquid;

[0040] The cleaned and polished zinc alloy substrate is coupled with an iron clamp and then surface adjusted;

[0041] The treated zinc alloy substrate is immersed in a aging solution for chemical conversion treatment to obtain a chemical conversion film. The preparation of the zinc phosphate chemical conversion film on the surface of the degradable zinc alloy is achieved by adding a film-forming substance and an accelerator to the conversion solution.

[0042] In some embodiments, the cleaned and surface-adjusted zinc alloy substrate is immersed in a aging solution;

[0043] Preferably, the method for cleaning the zinc alloy substrate comprises the following steps: ultrasonically cleaning the polished zinc alloy substrate with acetone, ethanol, and deionized water at room temperature for 10-15 minutes in sequence; and then washing with deionized water;

[0044] Preferably, the surface adjustment method of the zinc alloy substrate comprises the following steps: soaking in a 2-5 g / L colloidal titanium solution for 20-40 seconds;

[0045] Preferably, the temperature of the zinc alloy substrate surface is adjusted to 20-35°C.

[0046] In some embodiments, before the chemical conversion treatment, the pH value of the slaking liquid is adjusted to 2-3 using phosphoric acid or sodium hydroxide solution.

[0047] In some embodiments, the chemical conversion process is performed under ultrasonic field conditions;

[0048] Preferably, the ultrasonic power is 120-300W.

[0049] In some embodiments, the product is further washed and dried, wherein the washing step is rinsing with deionized water and the drying temperature is 20-40° C. When the temperature is too low, the drying is slow, and when the temperature is too high, the film layer dries quickly, which may cause partial microcracks in the film layer.

[0050] The present invention discloses a zinc phosphate chemical conversion film on the surface of a degradable zinc alloy and a preparation method thereof, comprising the following steps: preparing a chemical conversion solution containing phosphate ions, nitrate ions and an accelerator; subjecting the chemical conversion solution to an iron powder aging treatment to obtain an aging solution; coupling a cleaned and surface-activated zinc alloy substrate with an iron clamp and then immersing the substrate in the aging solution for chemical conversion treatment to obtain a chemical conversion film. The preparation of a zinc phosphate film layer on the surface of a degradable zinc alloy is achieved by designing the conversion time. The zinc phosphate chemical conversion film can inhibit the excessive release of zinc ions during the degradation process of the zinc alloy, achieve effective protection of the zinc alloy substrate, improve the biocompatibility and antibacterial properties of the zinc alloy, and has potential significance for further improving the clinical application effect of zinc alloy substrate implants.

[0051] The third aspect of the present invention provides a zinc phosphate chemical conversion film on the surface of a zinc alloy, the main phase composition of which is zinc phosphate (Hopeite, Zn 3 (PO 4 ) 2 ·4H 2 O); preferably, prepared by the above method.

[0052] A fourth aspect of the present invention provides a surface-modified zinc alloy, comprising a zinc alloy substrate and a zinc phosphate chemical conversion film attached to the surface of the zinc alloy substrate.

[0053] The fifth aspect of the present invention provides the use of the surface modified zinc alloy as an implant material.

[0054] Example 1

[0055] (1) Measure HNO 3 30ml, H 3 PO 4 17ml, NaClO 3 2g, Ca(NO 3 ) 2 ·4H 2 O 5g, C 6 H 8 O 7 ·H 2 O 5g, dissolved in 1L deionized water and mixed evenly to obtain the chemical conversion base solution;

[0056] (2) Weigh 1 g of reduced iron powder and mix with 7% v / v H 3 PO 4 After pickling for 5 minutes, add the mixture into the chemical conversion base solution, place it at room temperature for 24 hours, and filter the supernatant to obtain the aging solution;

[0057] (3) Using 10wt%H 3 PO 4 Or adjust the pH value of the aging liquid to 2.5 with 5mol / LNaOH solution;

[0058] (4) The polished zinc alloy substrate was ultrasonically cleaned with acetone, ethanol, and deionized water at room temperature for 10 min in sequence, and then placed in a 3 g / L colloidal titanium solution for conditioning at room temperature for 30 s;

[0059] (5) coupling the pure titanium substrate treated in step (4) with an iron clamp, and then immersing it in a aging solution and treating it in a 300W ultrasonic field environment at room temperature for 1 min;

[0060] (6) The product obtained in step (5) is rinsed with deionized water for several times and dried at room temperature for 1 hour to obtain a zinc phosphate chemical conversion film on the surface of the zinc alloy.

[0061] Example 2

[0062] (1) Measure HNO 3 30ml, H 3 PO 4 17ml, NaClO 3 2g, Ca(NO 3 ) 2 ·4H 2 O 5g, C 6 H 8 O 7 ·H2 O 5g, dissolved in 1L deionized water and mixed evenly to obtain the chemical conversion base solution;

[0063] (2) Weigh 1 g of reduced iron powder and mix with 7% v / v H 3 PO 4 After pickling for 5 minutes, add the mixture into the chemical conversion base solution, place it at room temperature for 24 hours, and filter the supernatant to obtain the aging solution;

[0064] (3) Using 10wt%H 3 PO 4 Or adjust the pH value of the aging liquid to 2.5 with 5mol / LNaOH solution;

[0065] (4) The polished zinc alloy substrate was ultrasonically cleaned with acetone, ethanol, and deionized water at room temperature for 10 min in sequence, and then placed in a 3 g / L colloidal titanium solution for conditioning at room temperature for 30 s;

[0066] (5) coupling the zinc alloy substrate treated in step (4) with an iron clamp, and then immersing it in a aging solution and treating it in a 300W ultrasonic field environment at room temperature for 5 minutes;

[0067] (6) The product obtained in step (5) is rinsed with deionized water for several times and dried at room temperature for 1 hour to obtain a zinc phosphate chemical conversion film on the surface of the zinc alloy.

[0068] Example 3

[0069] (1) Measure HNO 3 30ml, H 3 PO 4 17ml, NaClO 3 2g, Ca(NO 3 ) 2 ·4H 2 O 5g, C 6 H 8 O 7 ·H 2 O 5g, dissolved in 1L deionized water and mixed evenly to obtain the chemical conversion base solution;

[0070] (2) Weigh 1 g of reduced iron powder and mix with 7% v / v H 3 PO 4 After pickling for 5 minutes, add the mixture into the chemical conversion base solution, place it at room temperature for 24 hours, and filter the supernatant to obtain the aging solution;

[0071] (3) Using 10wt%H 3 PO 4 Or adjust the pH value of the aging liquid to 2.5 with 5mol / LNaOH solution;

[0072] (4) The polished zinc alloy substrate was ultrasonically cleaned with acetone, ethanol, and deionized water at room temperature for 10 min in sequence, and then placed in a 3 g / L colloidal titanium solution for conditioning at room temperature for 30 s;

[0073] (5) connecting the zinc alloy substrate treated in step (4) to an iron clamp, and then immersing it in a aging solution and treating it in a 300W ultrasonic field environment at room temperature for 10 minutes;

[0074] (6) The product obtained in step (5) is rinsed with deionized water for several times and dried at room temperature for 1 hour to obtain a zinc phosphate chemical conversion film on the surface of the zinc alloy.

[0075] Example 4

[0076] (1) Measure HNO 3 30ml, H 3 PO 4 17ml, NaClO 3 2g, Ca(NO 3 ) 2 ·4H 2 O 5g, C 6 H 8 O 7 ·H 2 O 5g, dissolved in 1L deionized water and mixed evenly to obtain the chemical conversion base solution;

[0077] (2) Weigh 1 g of reduced iron powder and mix with 7% v / v H 3 PO 4 After pickling for 5 minutes, add the mixture into the chemical conversion base solution, place it at room temperature for 24 hours, and filter the supernatant to obtain the aging solution;

[0078] (3) Using 10wt%H 3 PO 4 Or adjust the pH value of the aging liquid to 2.5 with 5mol / LNaOH solution;

[0079] (4) The polished zinc alloy substrate was ultrasonically cleaned with acetone, ethanol, and deionized water at room temperature for 10 min in sequence, and then placed in a 3 g / L colloidal titanium solution for conditioning at room temperature for 30 s;

[0080] (5) coupling the zinc alloy substrate treated in step (4) with an iron clamp, and then immersing it in a aging solution and treating it in a 300W ultrasonic field environment at room temperature for 15 minutes;

[0081] (6) The product obtained in step (5) is rinsed with deionized water for several times and dried at room temperature for 1 hour to obtain a zinc phosphate chemical conversion film on the surface of the zinc alloy.

[0082] Figure 1 The X-ray diffraction pattern of the zinc phosphate chemical conversion film on the surface of the zinc alloy is described. From the pattern analysis, it can be seen that the phase composition of the conversion film obtained in Examples 1-4 (i.e., under different conversion times in the conversion solution) is all zinc phosphate crystal phase (Hopeite, Zn 3 (PO 4 ) 2 ·4H 2 O).

[0083] Figure 2 This is a field emission scanning electron microscope image of the zinc phosphate chemical conversion film on the surface of the zinc alloy. Figure 2 .A. Figure 2 .B. Figure 2 .C. Figure 2 .D correspond to the morphological characteristics of the zinc phosphate conversion film obtained in Example 1, Example 2, Example 3, and Example 4, respectively. It can be seen from the figure that when the conversion time is short, the zinc phosphate conversion film can evenly cover the surface of the zinc alloy substrate, the grains are small and uniform, and the film layer is dense and complete. As the reaction time is extended to 10 minutes, the film layer becomes thicker, and the film layer falls off in some areas. However, during this period, the change in conversion time has little effect on the morphology of the zinc phosphate conversion film. When the reaction time is 15 minutes, the morphology of the zinc phosphate film layer changes. At this time, the film layer can tightly cover the zinc alloy substrate, but the film layer still falls off in some areas. The above phenomena show that the preparation of zinc phosphate chemical conversion film on the surface of zinc alloy substrate can be achieved in a relatively short time.

[0084] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A modified zinc alloy with a zinc phosphate film layer coated on the surface, comprising a zinc alloy as a matrix and a zinc phosphate chemical conversion film coated on the surface of the zinc alloy matrix; The main phase composition of the zinc phosphate chemical conversion film is zinc phosphate; The method for preparing the modified zinc alloy with a surface coated with a zinc phosphate film layer comprises the following steps: Prepare a chemical conversion solution, the chemical conversion solution is composed of a phosphoric acid solution, a nitric acid solution and an accelerator; the accelerator is Ca(NO3)2·4H2O, NaClO3 and C6H8O7·H2O; The chemical conversion liquid is subjected to a reduction iron powder aging treatment to obtain an aging liquid; the pH value of the aging liquid is adjusted to 2.5 with phosphoric acid or sodium hydroxide solution; The cleaned and surface-adjusted zinc alloy substrate is coupled with an iron clamp and then immersed in the aging solution for chemical conversion treatment, and a zinc phosphate chemical conversion film is coated on the surface of the zinc alloy substrate to obtain a modified zinc alloy with a surface coated with a zinc phosphate film layer; the temperature of the chemical conversion treatment is 20-35° C., and the conversion time is 1-5 min; the chemical conversion treatment is carried out under ultrasonic field conditions; and the power of the ultrasonic field is 120-300 W; The surface adjustment comprises the following steps: soaking in a 2-5 g / L colloidal titanium solution for 20-40 seconds; the surface adjustment temperature of the zinc alloy substrate is 20-35°C.

2. A method for preparing a modified zinc alloy having a surface coated with a zinc phosphate film, comprising the following steps: Prepare a chemical conversion solution, wherein the chemical conversion solution is composed of a phosphoric acid solution, a nitric acid solution and an accelerator, wherein the accelerator is one or more of Ca(NO3)2·4H2O, NaClO3, NaNO3 and C6H8O7·H2O; The chemical conversion liquid is subjected to a reduction iron powder aging treatment to obtain an aging liquid; the pH value of the aging liquid is adjusted to 2.5 with phosphoric acid or sodium hydroxide solution; The cleaned and surface-adjusted zinc alloy substrate is coupled with an iron clamp and then immersed in the aging solution for chemical conversion treatment, and a zinc phosphate chemical conversion film is coated on the surface of the zinc alloy substrate to obtain a modified zinc alloy with a surface coated with a zinc phosphate film layer; the temperature of the chemical conversion treatment is 20-35° C., and the conversion time is 1-5 min; the chemical conversion treatment is carried out under ultrasonic field conditions; and the power of the ultrasonic field is 120-300 W; The surface adjustment comprises the following steps: soaking in a 2-5 g / L colloidal titanium solution for 20-40 seconds; the surface adjustment temperature of the zinc alloy substrate is 20-35°C.

3. The preparation method according to claim 2, characterized in that: The concentrations of the substances in the chemical conversion solution are: phosphoric acid 0.1-0.3 mol / L, nitric acid 0.3-0.6 mol / L, and accelerator 0.01-0.1 mol / L.

4. The preparation method according to claim 2, characterized in that: The aging treatment is as follows: adding 1-5 g of reduced iron powder to the chemical conversion liquid, and allowing to stand and mature at 20-35° C. for 12-24 hours to obtain a aging liquid.

5. The preparation method according to claim 2, characterized in that: The cleaning comprises the following steps: ultrasonically cleaning the polished zinc alloy substrate with acetone, ethanol and deionized water in turn at room temperature for 10-15 min; and then washing with deionized water.

6. The preparation method according to claim 2, characterized in that: After the chemical conversion treatment, the obtained product is further cleaned and dried. The cleaning step is to rinse with deionized water and the drying temperature is 20-40°C.

7. Use of the modified zinc alloy with a surface coated with a zinc phosphate film layer according to claim 1 or the modified zinc alloy with a surface coated with a zinc phosphate film layer obtained by the preparation method according to any one of claims 2 to 6 in the preparation of implant materials.

Citation Information

Patent Citations

  • Preparation method of zinc phosphate chemical conversion coating in hierarchical structure

    CN103924226A

  • Method of applying phosphate coatings to metal surfaces

    CN1169165A

  • Chemical conversion treatment liquid for metallic material and process for treatment

    US20110305840A1

  • Products of manufacture having enhanced biocompatibility and antibacterial properties and methods of making and using them

    US20200289710A1